Organocatalytic Asymmetric Conjugate Addition of Aldehydes to Maleimides and Nitroalkenes in Deep Eutectic Solvents - Alejandro Torregrosa-Chinillach; Alba Sánchez-Laó; Elisa Santagostino; Rafael Chinchilla (Molecules, 2019)
A chiral primary amine-salicylamide is used as an organocatalyst for the enantioselective conjugate addition of α,α-disubstituted aldehydes to maleimides and nitroalkenes. The reactions are performed in deep eutectic solvents as reaction media at room temperature, leading to the corresponding adducts with enantioselectivities up to 88% (for maleimides) and 80% (for nitroalkenes). Catalyst and solvent can be recovered and reused.